A Multi‑Center, Open‑Label, Single‑Arm Trial to Evaluate the Efficacy, Pharmacokinetics, and Safety and Tolerability of IGSC 20% in Subjects with Primary Immunodeficiency - Santamaria, Manuel; Neth, Olaf; Douglass, Jo A; Krivan, Gergely; Kobbe, Robin; Bernatowska, Ewa; Grigoriadou, Sofia; Bethune, Claire; Chandra, Anita; Horneff, Gerd; Borte, Michael; Sonnenschein, Anja; et al. (Journal of clinical immunology, 2022)
PURPOSE: The purpose of this phase 3 study was to evaluate the efficacy, pharmacokinetics (PK), and safety of Immune Globulin Subcutaneous (Human), 20% Caprylate/Chromatography Purified (IGSC 20%) in patients with primary immunodeficiency (PI). METHODS: Immunoglobulin treatment-experienced subjects with PI received 52 weeks of IGSC 20% given weekly at the same dose as the subject's previous IgG regimen (DAF 1:1); the minimum dose was 100 mg/kg/week. The primary endpoint was serious bacterial infections (SBIs [null vs alternative hypothesis: SBI rate per person per year ≥ 1 vs < 1]). IgG subclasses and specific pathogen antibody levels were also measured. RESULTS: Sixty-one subjects (19 children [≤ 12 years], 10 adolescents [> 12-16 years], and 32 adults) were enrolled. The rate of SBIs per person per year was 0.017. The 1-sided 99% upper confidence limit was 0.036 (< 1), and the null hypothesis was rejected. The rate of hospitalization due to infection per person per year was 0.017 (2-sided 95% confidence interval: 0.008-0.033) overall. The mean trough total IgG concentrations were comparable to the previous IgG replacement regimen. The average of the individual mean trough ratios (IGSC 20%:previous regimen) was 1.078 (range: 0.83-1.54). The average steady-state mean trough IgG concentrations were 947.64 and 891.37 mg/dL, respectively. Seven subjects had serious treatment-emergent adverse events (TEAEs); none was drug-related. The rate of all TEAEs, including local infusion site reactions, during 3045 IGSC 20% infusions was 0.135. Most TEAEs were mild or moderate. CONCLUSIONS: IGSC 20% demonstrated efficacy and good safety and tolerability in subjects with PI.
Keywords: syndromy imunologické nedostatečnosti; Immunologic Factors; GTI1503; Immunoglobulin G; Adolescent; intravenózní imunoglobuliny; Child; 20% immunoglobulin; dítě; Adult; imunoglobulin G; dospělí; Immunoglobulins, Intravenous; mladiství; Primary immunodeficiency; lidé; Humans; Immunologic Deficiency Syndromes; subcutaneous; imunologické faktory; immunoglobulin replacement therapy; subkutánní infuze; Infusions, Subcutaneous